Can Clinician-Stabilization with Hand-Held Dynamometry Yield a Reliable Measure of Knee Flexion Torque? - Daniel Larson; Daniel Lorenz; Brittany Melton (North American Sports Medicine Institute, 2022)
# Background Assessment of knee flexion torque is a relevant clinical measure following various injuries and surgeries to determine progress in rehabilitation and inform decision making. A variety of methods using hand-held dynamometry have been shown to be reliable in obtaining this measure, and typically require a means of external fixation or stabilization. Clinically efficient methods of reliable clinician-stabilization are sparse in the literature. # Hypothesis/Purpose Determine inter and intra-rater reliability of two clinically efficient methods of assessing isometric knee flexion torque using hand-held dynamometry with clinician-stabilization. The hypothesis was that each method would yield good to excellent reliability. # Study Design Cross-Sectional Study # Methods Twenty healthy individuals were assessed by two clinicians on two separate days. During each session, knee flexion torque was assessed with hand-held dynamometry with two methods: 1) in the seated position with the hip and knee flexed to 90 degrees while the clinician stabilized the dynamometer between the participant's leg and table and 2) in prone with the hip at 0 degrees and knee at 90 degrees while the clinician assumed a stride stance with elbows locked in extension to stabilize the dynamometer on the participant's leg. Inter and intra-rater reliability were determined for each method. # Results ICC values were 0.88-0.94 and 0.77-0.90 for inter and intra-rater reliability respectively with the seated method. The prone method yielded ICC values of 0.84-0.96 and 0.89-0.94 for inter and intra-rater reliability respectively. MDC values ranged from 30-62% with the seated method and 21-40% with the prone method. # Conclusion Inter and intra-rater reliability were good to excellent for assessing knee flexion torque with hand-held dynamometry using both the seated and prone methods with clinically efficient clinician-stabilization approaches. The prone method may be more sensitive to detecting change over time due to lower MDC values. # Level of Evidence 2b